The object and the subject in scientific research - Luis Alberto Corona Martínez; Mercedes Fonseca Hernández; Yosbel Alvarez Alvarez (Medisur)
This article presents the dialectical unity between the object of study and the research subjects. Because usually, through the universe and the research sample, the subjects to be studied are declared, this work emphasizes the need to explicitly declare the object to be research.